Factors Influencing Career Choices of Students: An Empirical Examination of Some Aspects of the Neoclassical Theory of Choice in Labour Markets - David A. Dodge; Neil M. Swan (Queen's University, Department of Economics, 1971)
The factors which motivate a student to choose a particular career are many; the process of career choice is a complex one. Psychologists and sociologists stress the importance of factors such as need for achievement, peer group attitudes, family background, and cultural norms in their explanations of the choice process. Economists take these factors as given, and examine instead the relative importance of the econmic costs and benefits in the determination of career choice. The general purpose of this paper is to ascertain whether the assumptions of the economist's model are appplicable to the process of choice of career.
Keywords: 330